Pendekatan Metakognitif Untuk Keterampilan Membaca Bahasa Arab - Haniefa, Rifda (Ta'limi | Journal of Arabic Education and Arabic Studies, 2022)
Metacognition is a mental activity in the cognitive structure that is carried out consciously by a person to regulate, control, and examine his own thinking process. The same thing is to provide awareness to students how the learning process is in accordance with each individual's abilities, the needs that must be met in order to achieve success in learning and learning strategies that are in accordance with the skills to be achieved. This research is a qualitative study that produces descriptive data. The type of this research is library research. The data analysis used is content analysis. The application of a metacognitive approach to Arabic reading skills can be implemented by combining the metacognitive approach proposed by Najmi Hayati, Titin Susilowati, North Central Regional Education Laboratory (NCREL) and the Curriculum Development Center of the Ministry of Education Malaysia which is divided into three stages, namely the stage of the conscious learning process, Stage planning learning, as well as the stage of monitoring and reflection on learning. At each stage the researcher used the help of metacognitive learning journals and question yourself strategies to maximize the use of the metacognitive approach.